2009
DOI: 10.1002/jrs.2223
|View full text |Cite
|
Sign up to set email alerts
|

Surface enhanced Raman scattering of nano diamond using visible‐light‐activated TiO2 as a catalyst to photo‐reduce nano‐structured silver from AgNO3 as SERS‐active substrate

Abstract: In this work, we demonstrate nano-structured silver particles photo-reduced from silver nitride (AgNO 3 ) solution using visible-light-activated titanium dioxide (TiO 2 ), which can be a convenient and effective substrate for surface enhanced Raman spectroscopy (SERS) observation. Visible-light-activated carbon-containing TiO 2 nanoparticles are applied to photo-reduce and form nano-structured silver from AgNO 3 upon visible-light illumination. Photo-reduced nano-structured silver is used as an active substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The 'tetragonal anatase structured' TiO 2 belongs to D194h (I4 1 /amd) space group and following normal lattice A 1g +B 1g +B 2g +E g . 33 The first E g peak at ~144 cm -1 , a characteristic of anatase TiO 2 was formed in the as-prepared TNCs. The peaks at 516 (corresponding to B 1g , A 2g ) and 635 cm -1 (correspond to E g ) modes of anatase TiO 2 are observed.…”
Section: Resultsmentioning
confidence: 92%
“…The 'tetragonal anatase structured' TiO 2 belongs to D194h (I4 1 /amd) space group and following normal lattice A 1g +B 1g +B 2g +E g . 33 The first E g peak at ~144 cm -1 , a characteristic of anatase TiO 2 was formed in the as-prepared TNCs. The peaks at 516 (corresponding to B 1g , A 2g ) and 635 cm -1 (correspond to E g ) modes of anatase TiO 2 are observed.…”
Section: Resultsmentioning
confidence: 92%
“…As a wide-band gap semiconductor, TiO 2 is increasingly concerned in the SERS field nowadays. TiO 2 as an active substrate widens the application field for SERS in various areas, especially in photosensitive dye cell, , catalysis, biomedical, , and other industries. Meanwhile, the possible SERS mechanism on TiO 2 is discussed, which may help us understand the related SERS mechanism on semiconductor substrate as well as to understand the charge transfer process between adsorbates and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Humic substance have high molecular weight naturally occurring in yellow-brown, by using TiO 2 80% humic acid reduction is reported ( Liu et al ., 2008 ), in another paper 65% reduction in humic acid reported ( Valencia et al ., 2018 ) In organic pollutant present in waste water in the form of nitrates, halides, ammonia, cyanide and thiocyanate these pollutant an effectively decompose by photocatalytic process. Different semiconductors nanoparticles such as TiO 2 against AgNO 3 , TiO ( López-Muñoz et al, 2016 , Hong et al, 2009 ) ZnO against Cr(Vi) and potassium cyanides ( Joshi and Shrivastava, 2011 , Bagabas et al, 2013 ) and CdS/Titanate nanotubes reported against ammonia in water ( Lee et al ., 2002 ).…”
Section: Application Of Photo-catalystmentioning
confidence: 99%